Genotype-Phenotype diversity of Beta-Thalassemia in Malaysia: treatment options and emerging therapies - Elizabeth, G.; Ann, T.J.A.M. (Malaysian Medical Association, 2010)
The haemoglobinopathies and thalassemias represent the most common inherited monogenic disorders in the world. Beta-thalassaemia major is an ongoing public health problem in Malaysia. Prior to 2004, the country had no national policy for screening and registry for thalassemia. In the absence of a national audit, the true figure of the extent of thalassemia in the Malaysian population was largely presumptive from micro-mapping studies from various research workers in the country. The estimated carrier rate for beta-thalassemia in Malaysia is 3.5-4. There were 4768 transfusion dependent thalassemia major patients as of May 2010 (Data from National Thalassemia Registry).